(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the role and significance of spiritual and moral values in the military education system. Military conflicts of the 21st century demonstrate that combat success depends not only on technological superiority but also on the moral and psychological stability of personnel. The article analyzes the integration of historical experience—using “The Institutes of Timur” (Temur tuzuklari) as an example—and modern military pedagogical methods.